2005
DOI: 10.1002/ijc.21075
|View full text |Cite
|
Sign up to set email alerts
|

Black tea induces tumor cell apoptosis by Bax translocation, loss in mitochondrial transmembrane potential, cytochrome c release and caspase activation

Abstract: Recently the anti-cancer role of black tea has gained immense importance. Nevertheless, the signaling pathways underlying black tea-induced tumor cell death are still unknown. Previously we reported that black tea induces Ehrlich's ascites carcinoma (EAC) cell apoptosis by changing the balance between pro-and anti-apoptotic proteins. It is now well accepted that many cell death pathways converge at the mitochondria to decrease mitochondrial transmembrane potential (MTP) thereby releasing apoptogenic proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
(66 reference statements)
3
15
0
Order By: Relevance
“…The decrease in Bcl-2/Bax ratio observed in the present study can lead to a decrease in Dj m with subsequent activation of caspase-3 activity probably via the cytochrome c/Apaf-1/caspase-9 pathway. These findings are consistent with previous reports on the apoptosis inducing effects of tea polyphenols on various cancer cell lines (Bhattacharyya et al, 2005;Kundu et al, 2005;Nakazato et al, 2005a,b;Qanungo et al, 2005). In a recent report, we have demonstrated that combined administration of tea polyphenols and bLF inhibits hamster buccal pouch carcinogenesis by inducing apoptosis through decreasing Bcl-2/Bax ratio and increasing caspase-3 expression (Chandra Mohan et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in Bcl-2/Bax ratio observed in the present study can lead to a decrease in Dj m with subsequent activation of caspase-3 activity probably via the cytochrome c/Apaf-1/caspase-9 pathway. These findings are consistent with previous reports on the apoptosis inducing effects of tea polyphenols on various cancer cell lines (Bhattacharyya et al, 2005;Kundu et al, 2005;Nakazato et al, 2005a,b;Qanungo et al, 2005). In a recent report, we have demonstrated that combined administration of tea polyphenols and bLF inhibits hamster buccal pouch carcinogenesis by inducing apoptosis through decreasing Bcl-2/Bax ratio and increasing caspase-3 expression (Chandra Mohan et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Tea polyphenols are known to mediate their anticancer properties by induction of apoptosis (Bhattacharyya et al, 2005;Kundu et al, 2005;Nakazato et al, 2005a,b;Qanungo et al, 2005). The present results also demonstrate that green and black tea polyphenols inhibit the growth of CAL-27 cells by inducing apoptosis as revealed by characteristic changes in nuclear morphology and A o peak.…”
Section: Discussionsupporting
confidence: 75%
“…2) which showed that GTP has potential to regulate the transition of cells from G2 to M phase by down modulation of nuclear factor-kappaB [26]. Tea polyphenols are known to mediate their anti-cancer properties by induction of apoptosis [27,28]. The present study also supports the same notions as revealed by characteristic increase in cells in sub G1 peak of cell cycle and annexin-V and PI staining (Figs.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of apoptotic pathway is a key mechanism by which cytotoxic drugs kill cancer cells. Black tea, tanshinone IIA and other natural products inhibit tumor growth (Bhattacharyya et al, 2005: Wang et al, 2005Hsu et al, 2005). Nucleus condensation and apoptotic bodies appearance are universal characteristics of cells undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%